HUBUNGAN ANTARA MINAT BELAJAR DAN LINGKUNGAN BELAJAR DENGAN PRESTASI BELAJAR MATEMATIKA - Yuli Setya Hartanti; Esti Harini (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The purpose of the research was to find out correlate between  learn interest, and learning area with mathematics learning achievement on 10th  grade students at the whole district of Kalibawang Yogyakarta. The genre of this research is descriptive researchment. The population in this research were all students of 10th grade students at the whole district of Kalibawang Yogyakarta with amount 48 students and the samples taken at sampel jenuh with amount 48 students. Data collection method used was a questionannaire and a documentation. Analysis using descriptive analysis of data, multiple regression, and partial correlation. In the major hypothesis test is obtained R = 0,451 and R2 = 0,203 with sig=0,006 < 0,05. Then in the first minor hypothesis test is obtained ry1-2 = 0,297 with         sig=0,043 < 0,05; and the second minor hypothesis test is obtained ry2-1 = 0,343 with sig=0,018 < 0,05. So there is a positive and significant correlation between learn interest, and learning area with mathematics learning achievement on 10th  grade students at the whole district of Kalibawang Yogyakarta as collective and partial. It is expected that students care about learn interest, and learning area mathematics learning achievement increasingly.